2013
DOI: 10.1002/jaba.29
|View full text |Cite
|
Sign up to set email alerts
|

Conducting Functional Analyses of Problem Behavior via Telehealth

Abstract: Behavior consultants conducted functional analyses (FAs) via telehealth with 20 young children with autism spectrum disorders between the ages of 29 and 80 months who displayed problem behavior and lived an average of 222 miles from the tertiary hospital that housed the behavior consultants. Participants’ parents conducted all procedures during weekly telehealth consultations in regional clinics located an average of 15 miles from the participants’ homes. Behavior consultants briefly trained parent assistants … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

18
216
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 158 publications
(235 citation statements)
references
References 51 publications
(57 reference statements)
18
216
0
1
Order By: Relevance
“…Only children who completed FA and were started in FCT were included in the current analysis. Information on a subsample of children from group 1 was reported previously by Wacker et al 12 Wacker et al 5,11 reported selected data from 20 of the participants from group 2, and Suess et al 14 described treatment fidelity data from the first 3 participants in group 3. Among the 107 children who started FCT in these 3 groups, 8 discontinued treatment in group 1 (3 with ASD, 5 with other DD), 3 discontinued treatment in group 2, and 2 discontinued treatment in group 3.…”
Section: Childrenmentioning
confidence: 99%
See 3 more Smart Citations
“…Only children who completed FA and were started in FCT were included in the current analysis. Information on a subsample of children from group 1 was reported previously by Wacker et al 12 Wacker et al 5,11 reported selected data from 20 of the participants from group 2, and Suess et al 14 described treatment fidelity data from the first 3 participants in group 3. Among the 107 children who started FCT in these 3 groups, 8 discontinued treatment in group 1 (3 with ASD, 5 with other DD), 3 discontinued treatment in group 2, and 2 discontinued treatment in group 3.…”
Section: Childrenmentioning
confidence: 99%
“…5,11 Telehealth workstations were equipped with a Windows-based PC, video monitor, webcam, and headset. 21 For group 2, existing videoconferencing software was used at the hospital site.…”
Section: Telehealth Centermentioning
confidence: 99%
See 2 more Smart Citations
“…Clinic-to-Clinic (Wacker et al, 2013b) Clinic-to-Home Clinic-to-Clinic (Wacker et al, 2013b) Clinic-to-Home Clinic-to-Clinic (Wacker et al, 2013b Clinic-to-Home Fig. 1 Comparison of telehealth equipment needs between the clinic-to-clinic and clinic-to-home projects needs such as laptops and Ethernet cables being sent to the majority of families, and the need to install antivirus software on the laptops sent to the families.…”
Section: Used For Setupmentioning
confidence: 99%